Upaya Mediasi dan Akibat Hukum Sengketa Pertanahan di Kantor BPN Kabupaten Sambas - Jamiat, Jamiat; Saliro, Sri Sudono; Samsul, Samsul (Universitas Merdeka Madiun, 2021)
Abstract Land is considered an asset that promises high value, so it is not surprising that land disputes occur in order to maintain ownership rights to land. The land dispute resolution process can be carried out by litigation or non-litigation. In the context of the implementation of land dispute resolution conducted at the Sambas BPN office, it is carried out through a mediation process (non-litigation). Based on the facts in the field in 2018 and 2019, there were many land disputes that were not resolved through mediation. This research focuses on what factors are causing the failure of mediation conducted at the Sambas BPN Office and how the legal consequences of resolving land disputes are resolved through mediation. The research uses empirical methods, and is analytical descriptive. To obtain primary data observation and unstructured interviews were conducted with respondents and sampling using purposive sampling. The results showed that: first, the factors causing the failure of mediation were the factors of the parties, the completion time factor, and supporting data factors. Second, the legal consequences of resolving land disputes resolved through mediation bind the parties to the dispute.